Apocynin attenuates motility and induces transition from sustained to transient EGF-dependent Akt activation in MCF-7 cells that overexpress adaptor protein Ruk/CIN85 - Bazalii, A.V.; Drobot, L.B.; Komisarenko, S.V. (Вiopolymers and Cell, 2016)
Aim. To study a possible involvement of NADPH oxidases in the control of cell motility and Akt signaling in the human breast adenocarcinoma MCF-7 cells that stably overexpress the full-length form of adaptor protein Ruk/CIN85. Methods. Cell motility was studied by a transwell migration assay. The dynamics of EGF-induced Akt activation was investigated by Western blot analysis. Results. It has been shown that apocynin, an inhibitor of the assembly of plasma membrane NADPH oxidases, substantially attenuates the motility of Ruk/CIN85 overexpressing MCF-7 cells (subclone G10) in comparison with control cells. In addition, apocynin induced the transition from sustained to transient EGF-dependent Akt activation in G10 cells and did not influence transient Akt activation in control cells. Conclusions. The data obtained can suggest that ROS produced by NADPH oxidases are signaling components, upstream to Akt kinase, that mediate the increased migratory potential of Ruk/CIN85 overexpressing MCF-7 cells. Мета. З’ясувати можливе залучення NADPH оксидаз до контролю рухливості клітин і Akt-залежного сигнального шляху в аденокарциномних клітинах грудної залози людини лінії MCF 7, що стабільно надекспресують адаптерний протеїн Ruk/CIN85. Методи. Для аналізу рухливості клітин використовували модифіковану камеру Бойдена. Динаміку EGF-індукованої активації Akt досліджували Вестерн-блот аналізом. Результати. Було показано, що апоцинін, інгібітор збирання мембранних NADPH оксидаз, значно пригнічує рухливість клітин MCF-7, що надекспресують Ruk/CIN85 (субклон G10) у порівнянні з контрольними клітинами. Крім цього, апоцинін індукував перехід від тривалої до тимчасової EGF-індукованої активації Akt у G10 клітинах і не впливав на тимчасову активацію Akt у контрольних клітинах. Висновки. Отримані дані дозволяють припустити, що АФК, продукти NADPH оксидаз, є сигнальними компонентами, розташованими вище від кінази Akt, які опосередковують підвищений міграційний потенціал клітин MCF-7 з надекспресією Ruk/CIN85. Цель. Выяснить возможное вовлечение NADPH оксидаз в контроль подвижности клеток и Akt-зависимого сигнального пути в аденокарциномных клетках грудной железы человека линии MCF-7, которые стабильно сверхэкспрессируют адаптерный белок Ruk/CIN85. Методы. Для анализа подвижности клеток использовали модифицированную камеру Бойдена. Динамику EGF-индуцированной активации Akt исследовали Вестерн-блот анализом. Результаты. Было показано, что апоцинин, ингибитор сборки мембранных NADPH оксидаз, значительно угнетает подвижность клеток MCF-7, которые сверхэкспрессируют Ruk/CIN85 (субклон G10) по сравнению с контрольными клетками. Кроме этого, апоцинин индуцировал переход от длительной к временной EGF-индуцированной активации Akt в G10 клетках и не влиял на временную активацию Akt в контрольных клетках. Выводы. Полученные данные позволяют предположить, что АФК, продукты NADPH оксидаз, являются сигнальными компонентами, расположенными выше от киназы Akt, которые опосредуют повышенный миграционный потенциал клеток MCF-7 со сверхэкспрессией Ruk/CIN85.